A vegetação lenhosa da caatinga em assentamento do Estado de Sergipe : aspectos fitossociológicos, anatômicos e dendrocronológicos - Pagotto, Mariana Alves (2015)
In the semi-arid Caatinga of the Brazilian state of Sergipe, where the land is occupied predominantly by settlements of the agrarian reform, the principal products firewood, charcoal, and fence-posts are derived from forestry practices. With the aim of providing practical guidelines for the implementation of sustainable forestry management practices in these settlements, the present study analyzed the potential of local woody species as sources of timber. In this context, the socioeconomic and environmental characteristics of the Barra da Onça settlement in Poço Redondo (Sergipe) were identified, the structural and ecological traits of local plots of woodland were analyzed, and the anatomical traits of the wood of Poincianella pyramidalis (Tul.) L. P. Queiroz (catingueira) and Aspidosperma pyrifolium Mart. (pereiro) were described. This involved the collection of data on the quality of the wood, mean annual increment, and the identification of the environmental factors that determine growth patterns. For the socio-environmental analysis of the settlement, 22 local residents were interviewed using semi-structured questionnaires. For the botanical study, wandering-quarter surveys and hemispherical photographs were used to characterize the structure of the vegetation and canopy dynamics, respectively. The characteristics of the wood of P. pyramidalis and A. pyrifolium and its responses to environmental variables were examined using the traditional methods of wood anatomy, classic dendrochronology and X-ray densitometry. The results indicated that, while the settlement has adequate infrastructure, there are many limitations in terms of educational opportunities, the productivity of local agricultural practices, and the diversification of economic activities. The local rain-fed agriculture system and livestock practices are not ecological sustainable, and the socioeconomic consequences are apparent in fluctuations of productivity, the migration of settlers, and the degradation of the Caatinga. The vegetation of the settlement was dominated by a number of pioneer species, reflecting its exploitation by the local population. The wood of both P. pyramidalis and A. pyrifolium presented anatomical adaptations typical of xeric environments, and annual growth rings, permitting the construction of tree-ring chronologies, which presented annual variation closely correlated with rainfall levels and the surface temperature of the Atlantic Ocean. Poincianella pyramidalis, the most abundant species in the study area, had thicker fibers and a large amount of cellulose, reulting in high density wood (1.10 ± 0.13 g/cm3). Due to these features, this species is well adapted for the production of firewood in the rural settlements of Sergipe. These findings may contribute to the development of forest management practices in the local settlements, potentially providing an additional source of income in a sustainable way.